Penerapan Pemberian Aromaterapi Lavender terhadap Kualitas Tidur Lansia di Panti Harapan Ibu Ngaliyan Kota Semarang - Helsy Kusumaningrum; Menik Kustriyani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Sleep disturbances in the elderly are a health issue associated with physiological and psychological changes, as well as degenerative diseases, which lead to a decline in quality of life. This study aims to analyze the effects of lavender aromatherapy on sleep quality among the elderly at the Panti Harapan Ibu Ngaliyan nursing home in Semarang. The study employed a quantitative approach using a descriptive case study design involving five elderly individuals experiencing sleep disturbances. Data collection was conducted using the Pittsburgh Sleep Quality Index (PSQI) through observation and interviews before and after the intervention. Lavender aromatherapy was administered for seven consecutive days via inhalation using five drops of lavender on a cotton pad for fifteen minutes before bedtime. The results showed a decrease in PSQI scores among all participants, shifting from the “poor” category to “fair” and “good.” Changes in sleep quality were marked by a reduction in sleep latency, a decrease in the frequency of nighttime awakenings, and an increase in feelings of comfort and refreshment upon waking. Lavender aromatherapy proved effective as a non-pharmacological intervention in improving the sleep quality of the elderly both physiologically and psychologically.